Quantification of litter in cities using a smartphone application and citizen science in conjunction with deep learning-based image processing - Kako, Shin'ichiro (Waste management (New York, N.Y.), 2024)
Copyright © 2024 The Author(s). Published by Elsevier Ltd.. All rights reserved.